KAPASITAS ANTIOKSIDAN DAN INHIBITOR ALFA GLUKOSIDASE EKSTRAK UMBI BAWANG DAYAK [Antioxidant and Alpha-Glucosidase Inhibitory Properties of Bawang Dayak Bulb Extracts] - Andi Early Febrinda; Made Astawan; Tutik Wresdiyati; Nancy Dewi Yuliana (Jurnal Teknologi dan Industri Pangan, 2013)
Bawang dayak (Eleutherine palmifolia) is an indigenous plant in Borneo traditionally used by Dayak tribes to treat any kind of degenerative deseases including diabetes mellitus. The purpose of this research was to measure antioxidant and antidiabetic capacities of water and ethanolic extracts of bawang dayak bulb. Parameters evaluated in this research were phytochemical screening, total phenolics, flavonoid content, DPPH free-radical scavenging activity, and alpha glucosidase inhibiting (AGI) activity. The result showed that the total phenolics and flavonoid content in bawang dayak ethanolic extract (217.71 mg GAE/g and 65.35 mg QE/g) were higher than that of the water extract (139.93 mg GAE/g and 16.95 mg QE/g). The ethanolic extract also had higher antioxidant and AGI activities (IC50 112 and 241 ppm) than that of the water extract (IC50 526 and 505 ppm). In addition, the IC50 values for AGI in bawang dayak ethanolic extract was lower than acarbose which is known as a commercial antidiabetic agent.